Can electrochemically active biofilm protect stainless steel used as electrodes in bioelectrochemical systems in a similar way as galvanic corrosion protection? - Shamsuddin, Raba'atun Adawiyah; Abu Bakar, Mimi Hani; Daud, Wan Ramli Wan; Hong, Kim Byung; Jahim, Jamaliah Mat (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
Stainless steel (SS) has been reported as a suitable electrode material for the growth of electrochemically active biofilm whether it is for a microbial fuel cell (MFC) or microbial electrolysis cell (MEC) in the bioelectrochemical system. Although the flame oxidation technique could improve SS property as electrodes, it comes with an increased risk of corrosion. The undesirable corrosion may cause the release of a toxic element such as chromium. At present, mitigation actions have been identified such as connecting iron to a sacrificial metal in a mechanism known as galvanic corrosion protection (GCP). An external power source could be used as an alternative to supply current similar to the sacrificial metal, which technique applied in MEC. In this review, the electron flow mechanisms between microbiologically influenced corrosion (MIC) and MEC biocathode will be addressed. Thus, it proposes a hypothesis of SS protection from corrosion in a similar way as in the GCP. (C) 2019 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.